MODES OF INTERACTION BETWEEN SPERMATOZOID ABNORMALITIES AND CYTOKINES IN SEMINAL PLASMA FROM INFERTILE MALES - B. I. Aisikovich (SPb RAACI, 2014)
Abstract. Spearman rank correlation analysis was applied to assess some interrelations between morphological abnormalities of spermatozoids in males with long-term infertility, and cytokine levels in their seminal plasma. Such statistical analysis has revealed a significant positive correlation between prevalence of morphologically abnormal spermatozoids and the levels of IL-1β, MIP-1β, G-CSF, along with negative relationship with IL-5 and IL-10 contents in seminal fluid. The data are, generally, demonstrating participation of cytokines in regulation of male fertility. (Med. Immunol., 2008, Vol. 10, N 2-3, pp 203-208).